Near‐Global Variability of Stratospheric Water Vapor Observed by SAGE III/ISS. Issue 7 (30th March 2021) - Park, Mijeong; Randel, William J.; Damadeo, Robert P.; Flittner, David E.; Davis, Sean M.; Rosenlof, Karen H.; Livesey, Nathaniel; Lambert, Alyn; Read, William
Abstract: The Stratospheric Aerosol and Gas Experiment III instrument on the International Space Station (SAGE III/ISS) has been making high quality solar occultation measurements of stratospheric water vapor since June 2017. Here we evaluate the large‐scale geophysical variability of the SAGE III/ISS water vapor measurements for the first 3 years of observations (2017–2020) as part of data validation for retrieval version 5.1 (v5.1). Detailed comparisons of SAGE III/ISS v5.1 with the Aura Microwave Limb Sounder (MLS) version 5 retrievals show overall excellent agreement in terms of seasonal mean structure and large‐scale variability. SAGE III/ISS data capture the well‐known seasonal variations in water vapor including the vertically propagating "tape recorder" in the tropics and lower stratospheric maxima linked to the NH summer monsoons. The high vertical resolution (∼2 km) measurements from SAGE III/ISS demonstrate contributions of the monsoons to the wet phase of "tape recorder" during the Northern Hemisphere (NH) summer. Interannual variations over the short data record are also consistent between SAGE III/ISS and MLS in the stratosphere between 16 and 30 km. We furthermore evaluate large‐scale variations in relative humidity (RH) derived from the high vertical resolution SAGE III/ISS water vapor measurements, highlighting the detailed seasonal behavior and links to thermal structure near the tropical tropopause. Spatial distributions of RH at the cold point tropopause (CPT) show a close link between high RH and the minimum CPT temperature in both the NH winter and summer, consistent with temperature control of water vapor near the tropopause. Key Points: Geophysical variability of the H2 O from the Stratospheric Aerosol and Gas Experiment III on the International Space Station (SAGE III/ISS) are evaluated Seasonal and interannual variations in stratospheric water vapor are consistent between SAGE III/ISS and Microwave Limb Sounder Large‐scale variations in relative humidity highlight temperature control of water vapor near the tropopause